The Factors That Affecting Exclusive Breastfeeding In The Working Area Of Public Health Center Pabuaran, Serang District, 2020 - Ratu Rohima; Herman Sudirman; Yeny Sulistyowati (Journal of Ageing And Family, 2022)
Health is one aspect of community life, quality of life, labor productivity, high morbidity and mortality rates in infants and children. Breastmilk (ASI) is the best food for babies, especially babies aged 0-6 months, whose function cannot be replaced by any food and drink. Breastfeeding is the fulfillment of the rights of every mother and child. The research used is a quantitative method with a "cross sectional" approach, with accidental sempling data collection techniques, using an instrument in the form of a questionnaire. The number of sempel was 100 respondents. This study used univariate, bivariate and multivariate analysis with a confidence level of 95%. The results showed that of the 100 samples studied, there were mothers who gave exclusive breastfeeding as much as 45%. educate mothers who do not provide exclusive breastfeeding as much as 55%. based on the results of the study there is a significant relationship between maternal age, mother's education, mother's occupation, mother's parity and family income with exclusive breastfeeding. There are dominant factors that influence exclusive breastfeeding in the working area of Pabuaran Public Health Center, Serang Regency.Keywords: Infants, exclusive breastfeeding, age, education, parity, work and income